2017
DOI: 10.1038/nri.2017.140
|View full text |Cite
|
Sign up to set email alerts
|

The dawn of vaccines for cancer prevention

Abstract: An important role of the immune system is in the surveillance for abnormal or transformed cells, which is known as cancer immunosurveillance. Through this process, the first changes to normal tissue homeostasis caused by infectious or other inflammatory insults can be detected by the immune system through the recognition of antigenic molecules (including tumour antigens) expressed by abnormal cells. However, as they develop, tumour cells can acquire antigenic and other changes that allow them to escape elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
169
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(171 citation statements)
references
References 131 publications
2
169
0
Order By: Relevance
“…6,15,16 In this study, we showed that an agonistic anti-TLR4 mAb induces tumour-specific immune responses in mice immunized with a tumourspecific Ag, which enhanced the therapeutic efficacy of the anti-PD-1 mAb. 6,15,16 In this study, we showed that an agonistic anti-TLR4 mAb induces tumour-specific immune responses in mice immunized with a tumourspecific Ag, which enhanced the therapeutic efficacy of the anti-PD-1 mAb.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…6,15,16 In this study, we showed that an agonistic anti-TLR4 mAb induces tumour-specific immune responses in mice immunized with a tumourspecific Ag, which enhanced the therapeutic efficacy of the anti-PD-1 mAb. 6,15,16 In this study, we showed that an agonistic anti-TLR4 mAb induces tumour-specific immune responses in mice immunized with a tumourspecific Ag, which enhanced the therapeutic efficacy of the anti-PD-1 mAb.…”
Section: Discussionmentioning
confidence: 69%
“…This possibility suggests that OVA/anti-TLR4 mAb therapy may be effective against some MHC I-negative tumours. [15][16][17]35 Thus, most tumour Ags expressed exclusively or preferentially by tumours, but not normal tissues, are likely not suitable targets for tumour vaccine therapy. 46 Whereas EG7 and MC38 cells secrete OVA extracellularly, B16F10 cells retain OVA intracellularly because the transfected OVA lacks a signal peptide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[32,37] It is better that the immunosuppressive tumoral microenvironment was concurrently inhibited to reduce the escape of cancer cells from the immunosurveillance by the immune system. Commonly, cellular immune response is essential for cancer immunotherapy, and CD8 + effector T cells have to infiltrate the tumor tissue to eliminate tumor cells.…”
mentioning
confidence: 99%